1994
DOI: 10.1159/000204132
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood Progenitor Cell Transplantation Estimated by Three-Colour (CD34, HLA-DR, CD33) Flow Cytometry

Abstract: The relationships between transfused cell number of CD34+ cell subpopulations divided by HLA-DR and CD33 antibodies and hematopoietic recovery patterns after peripheral blood progenitor cell transplantation (PBPCT) subsequent to myeloablative chemoradiotherapy were investigated in 14 children with cancer. Both logarithm of transfused CD34+ cell number/106/kg and logarithm of transfused cell number/106/kg of the CD34+HLA-DR+CD33+ sub-population, which is supposed to be myeloid-committed ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 7 publications
1
13
1
Order By: Relevance
“…However, many investigators did not find any linear correlation between the number of infused CD34' cells and neutrophil engraftment, and had instead attempted to define CD34' cell threshold values above those where prompt engraftment occurs with increasing confidence. Threshold CD34' cell values varying from 2 to 5 X 106/kg have been suggested to be necessary to achieve rapid neutrophil and platelet recovery from BC infusion [5,10,[13][14][15]. In fact, our present study found a linear correlation between the time to recovery of PB cell counts postautograft and the absolute number of CD34' cells in the graft.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…However, many investigators did not find any linear correlation between the number of infused CD34' cells and neutrophil engraftment, and had instead attempted to define CD34' cell threshold values above those where prompt engraftment occurs with increasing confidence. Threshold CD34' cell values varying from 2 to 5 X 106/kg have been suggested to be necessary to achieve rapid neutrophil and platelet recovery from BC infusion [5,10,[13][14][15]. In fact, our present study found a linear correlation between the time to recovery of PB cell counts postautograft and the absolute number of CD34' cells in the graft.…”
Section: Discussionsupporting
confidence: 52%
“…Most investigators now insist on the powerful predictive role of the graft content in CD34' cells in optimally predicting the rapidity of the further engraftment kinetics [4,5,10,131. However, many investigators did not find any linear correlation between the number of infused CD34' cells and neutrophil engraftment, and had instead attempted to define CD34' cell threshold values above those where prompt engraftment occurs with increasing confidence.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting Milan/Mulhouse manual is still a valuable procedure reference in laboratory practice. 9,10 The subsequent years have resulted in several publications about the standardisation of flow cytometry analysis [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] as well as reports on the clinical implication of the enumeration of CD34 ϩ cells. 24,[26][27][28][29][30][31][32][33][34][35][36][37] The CD34 antigen is stage-specific and identifies cells in the early stages of haemopoietic differentiation.…”
Section: First Step In Quality Assessment Was Cd34 Standardisationmentioning
confidence: 99%
“…In the first phase, the CD34 technique was established in the laboratory and analysed for specificity, sensitivity, reproducibility and accuracy. [5][6][7][8][9][10][16][17][18][19][20][21][22][23][24][25][26] The subsequent second phase, documented a likely clinical influence by single centres analysing retrospective material/data. [27][28][29][30][31][32][33][34]36,37 The third phase prepared convincing single centre prospective evaluation [51][52][53][54][55][56][57][58] evolving into the most important phase four, a multicentre prospective evaluation based upon important clinical end-points (Table 2).…”
Section: The Final Step In Quality Assessment Is Clinical Validationmentioning
confidence: 99%
See 1 more Smart Citation